Cursinho Popular da Unesp de Franca: vivências e perspectivas de estudantes trabalhadores - Soares, Maísa Stefani (Universidade Federal de São Carlos, 2019)
The “Cursinho Popular da Unesp – S.E.U (University Extension Service)” is a popular preuniversity preparatory course, located at the city of Franca-SP. Founded in 1997, it serves socioeconomically disadvantaged students from the city and region. Franca-SP is a city nationally known as the pole of men’s shoe production, due to the growth of the footwear industry that until this day remains its main income source. Therefore, there was an intense outsourcing process that affected this industry by the 1990s. That was when the so-called “bancas de pesponto” - small home-based factories - had their expansion and dominated the Franca’s families backyards and garages. Consequently, this provision of service through the “bancas” has developed an environment permeated with unhealthy conditions, where it is possible to observe the devaluation of women’s work and the existence of child labor. Child labor is seen as an assistance to the production and it’s considered a way of educating children. This context is a common part of the city’s youth path, including the young people who were or are still part of the S.E.U. project. The main objective of this dissertation is to build S.E.U. alumni narratives based on the oral history methodology and on diverse methods of collecting information. In this work, there are six stories from alumni who participated in the project from 2013 to 2016, years in which I was a coordinator and student-teacher on the project. Those students memories were collected through conversations, recordings, and readings that served as research methods. Thus, it's possible to conclude the importance of spaces such as the S.E.U., which promotes the possibility of accessing Higher Education institutions to the most popular classes. It also exposes the experiences that those socially vulnerable groups have been submitted to, and how they are the results of the city's labor context.
Keywords: Juventudes; Educação Superior; Cursinho Popular; História Oral; Franca-SP; Youth; Higher education; Popular pre-university preparatory; Oral history; CIENCIAS HUMANAS::EDUCACAO